An analysis of the mobile library of St. Luke's Medical Center in Quezon City - Putong, Francis John D.; Dela Torre, Nathalie N. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
The St. Luke's Medical Center, one of the most advanced health institutions in the country to date, has lived to its trademark of pioneering in programs for the benefit of their patient clientele. With this, they started their mobile library service on August of 2000. It was with the purpose of presenting comprehensive information about the present state of this in-house mobile library, and determining its effectivity, that this thesis was undertaken. It is also sought to recommend solutions to the problems faced by bookmobiles as an approach to contributing knowledge to different user groups.
The study was conducted during the 2nd semester of the academic year 2002-2003. Survey questionnaires for the chief librarian and the library assistant in-charge as well as for the library users/clientele, who are the patients and their visitors, were distributed and requested to be answered. Personal interviews and document analysis were also employed.
The results of the study revealed that the in-house mobile library has quite a small but fairly sufficient collection, since library users usually do not stay long there and hence, do not get tired with the limited reading materials the collection has. The collection is limited to books and magazines. The reading materials can be borrowed and/or purchased by the clientele. Audio-visual materials are not available from the mobile library. It was also found out that there are two major concerns with the operations of the mobile library: 1st, the limited budget; and 2nd, the incidence of losses and unreturned materials. It is proposed that the 1st concern be addressed to the management of the health institution so that they could allot a bigger budget. The 2nd concern, with regards to the loss of reading materials, was recommended to be dealt with by better implementing the borrowing policy. Even though the mobile library is faced with these difficulties, operations still continue day by day. And the good thing is that, besides the technical and financial deficiencies that the program has at the present, the clientele still finds the mobile library service and the accommodating staff a good experience in their stay in such a health institution. Indeed, this mobile program serves as a very important tool in information dissemination as well as in providing an alternative source of recreation during their stay there.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: St. Luke's Medical Center Library; Book mobiles -- Philippines -- Quezon City